A formative measurement approach for exploring how to form service quality in hot spring resorts. (January 2019) - Liu, Xiaoming; Fu, Yi; Chao, Ren-Fang; Li, Jun (Justin)
In contrast to the reflective perspective of service quality measurement used in the existing literature, this paper proposes a multi-dimensional model for measuring service quality in hot spring resorts, based on a formative perspective. The formative measurement approach aims to explore how the service quality of hot spring resorts is formed. To achieve this purpose, an exploratory research study was conducted using partial least squares structural equation modelling method. A hot spring resort located in southern China was chosen as the research site to obtain the original data, by surveying customers with spa experience at the resort. Concurrently, service quality was investigated as a second-order construct using a reflective–formative model. Theoretically, this reflective–formative model provides a more comprehensive understanding of service quality in hot spring resort domains. Finally, this study confirmed the following six components of service quality for hot spring resorts: water quality, customer service, facilities, surroundings, alternative activities and convenience. The results show that these six components form service quality in hot spring resorts and may influence consumers' attachment to such places.